"Au plus dru!" L’influence de la Route sur les petites revues précédant l’Hexagone - Tellier, Christine (Voix et Images, 2002)
Keywords: Édition

25e anniversaire : Salon du livre de Montréal - Massicotte, Diane (Le salon, 2002)
Keywords: Expositions; Journalistes; Écrivains; Édition

From Bourassa to Bourassa: Wilderness to Restoration - MacDonald, L. Ian (McGill-Queen's University Press, 2002)
"From Bourassa to Bourassa is a narrative history of the Quebec Liberal Party during its wilderness years after the 1976 election of the Parti Quebecois and its subsequent restoration in 1985." "First published to critical acclaim in 1984, From Bourassa to Bourassa, 2nd edition, updates the story with Bourassa's landslide election victory in 1985 and his subsequent role in the Meech Lake Accord and the Canada-U.S. Free Trade Agreement, the two issues that largely defined the decade of the 1980s for Quebec and for Canada."--BOOK JACKET.
Keywords: Bourassa, Robert; Partis politiques

Women’s Workplaces: The Impact of Technological Change on Working-Class Women in the Home and in the Workplace in Nineteenth Century Montreal - Bradbury, Bettina (Rethinking Canada. The Promise of Women’s History, 2002)
Keywords: Femmes; Travail

Papineau: son influence sur la pensée canadienne: essai de psychologie historique - Circé-Côté, Ève (Mémoire des Amériques, 2002)
Keywords: Circé-Côté, Éva; Papineau, Louis-Joseph

L'industrie de la chaussure à Montréal, 1840-1870: le passage de l'artisanat à la fabrique - Burgess, Joanne (Travail et syndicalisme: naissance et évolution d'une action sociale, 2002)
Keywords: Artisans; Chaussure

Travail et syndicalisme: naissance et évolution d'une action sociale - Thwaites, James D. (Presses de l'Université Laval, 2002)
Keywords: Travail

Lettres à Paul-Émile Borduas - Gauvreau, Claude (Presses de l'Université de Montréal, 2002)
Keywords: Borduas, Paul-Émile; Écrivains

Discours sur la tolérance - Dessaulles, Louis Antoine (XYZ, 2002)
Keywords: Institut canadien; Journalistes; Écrivains